Razmerje osebek proti osebkov odvisnik v slovenskih povedih - Žele, Andreja (Slavistična revija, 2017)
The article deals with the position of the subject clause from the point of view of structural systemic parallelism, taking into account transformational possibilities in the relation sentence constituent vs. sentence constituent that has a form of a clause. In this context, the author also discusses the specificity of the predicative relationship between the subject and the predicate in a simple sentence.
Keywords: oseba; osebek; osebkov odvisnik; prisojevalno razmerje; Slovene; slovenščina; stavčni členi; zložena poved